Prevalence of Intestinal Parasitosis Among School Children in Baglung District of Western Nepal - Shrestha, A; Narayan, KC; Sharma, R (Kathmandu University Medical Journal, 2012)
Background This study was carried out to estimate the prevalence of intestinal parasites among school-going children of the Baglung municipality from December 2010 to January 2011. Objective To find out prevalence of parasitosis among school aged children and to make necessary recommendations for preventive measures. Method A total of 260 stool samples were collected. A structured questionnaire was used to collect data on predisposing factors. Nails were observed without prior information to the subjects so as to find their hygienic practice. The stool samples were examined by direct wet mount and formal ether concentration technique. Results The total prevalence of the intestinal parasitosis was found to be 21.05%. The prevalence for individual parasites was as follows: Entamoeba histolytica (9.23%), Giardia lamblia (5.76%), Trichuris trichuria (5%), Ancylostoma duodenale (2.65%) and Ascaris lumbricoides (2.3%). Nail hygiene and level of education were significantly associated with intestinal parasitosis. The gender and age of the children, sanitary habits including toilet use, hand washing practice, and the use of the antihelminthic drug (albendazole) were not significantly associated with intestinal parasitosis. Higher prevalence was seen in boys, children belonging to age group 10-14 years, lower secondary students, among those who reported gastrointestinal problems within last six months, children from agriculture-based families and children with untrimmed nail. Conclusion Major contributors for the prevalence of parasites were found to be poor personal hygiene and educational level of the children. Health education and mass treatment are recommended as a preventive measures. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 3-6 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6904